Service performance measures: a case study of quantity surveying branch Jabatan Kerja Raya Sarawak / Hartini Ismail - Ismail, Hartini (2009)
The purpose of this research is to determine the level of internal customer’s satisfaction towards Quantity Surveying Branch of Jabatan Kerja Raya Sarawak at the headquarters level which involves eleven branches and two units at Jabatan Kerja Raya Sarawak head office housed at Wisma Saberkas.